Pengaruh Kecemasan dan Motivasi Belajar dalam Pembelejaran Daring di Masa Pandemi Covid-19 Terhadap Hasil Belajar Sosiologi Siswa Kelas XII SMA Batik 1 Surakarta - Savitri, Ainun Rawie Eka; Rahman, Abdul; Hermawan, Yosafat (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Abstract. This study aims to examine the relationship between anxiety, and learning motivation with sociology learning outcomes. This research method used in this study is a quantitative correlation with cross-sectional research design. The population of the research were the twelfth grade students of Batik 1 Surakarta High School. Sample of the research were 132 students who selected using sample random sampling technique. Data of the research were collected through documentation and questionnaire. Data analyzed using correlation product-moment analysis and multiple regression analysis.Based on the Multiple Regression Test, the equation model Y = 50,992 + 0,073X1 + 0,417X2. Based on the Correlation Coefficient Test, the results show that: (1) there were not a correlation and not significant between anxiety with the sociology learning outcomes (rhitung =  > rtabel = 0,168 < 0,1697 ; p > 0,05); (2) there were a positive and significant correlation between learning motivation with the sociology learning outcomes (rhitung =  > rtabel = 0,485 > 0,1697 ; p < 0,05): (3) there were a significant correlation between anxiety and learning motivation with the sociology learning outcomes (Rxy > Rtabel = 0,509 > 0,1697 ; Sig F Change = 0,000 < 0,05).